Exoneration Clausula In The Goods Delivery Agreement Throughdelivery Service - Shinta Fawzia Kironowarni,; Wiwin Yulianingsih (VJJ, 2019)
Research entitled "Exoneration Clause in the Goods Delivery Agreement through the Delivery Service", due to the Exoneration Clause, it can harm consumers. Issues discussed regarding the form of exoneration clauses in goods delivery agreements through shipping services and legal protection for owners of goods that are harmed due to exoneration clauses. The study uses a normative approach and a concept approach, a conclusion is obtained as follows. The form of the exoneration clause in the goods delivery agreement via the shipping service is the contents of the exoneration clause that has binding power for the parties involved in it, the contents of the exoneration clause that do not have binding power for the parties involved in it. The exoneration clause has binding power for the parties involved in it as signed. Regarding the location, form and disclosure of standard clauses, it can also be seen from the intention of the business actor, that the obligation of the business actor is in good faith in carrying out his business activities. Legal protection for the owner of the goods that is harmed by the exoneration clause is a protection given to legal subjects in the form of legal instruments both preventive and responsive, both written and unwritten. If something happens to the goods sent, such as lost or damaged, it would be better if between the shipping service and the consumer together to resolve the case by way of peace first. Consumers can submit a claim first after that the freight forwarder can process the loss in accordance with the agreement and does not need to involve the court or the Dispute Settlement Agency (BPSK).